"The good, the bad and the ugly": professional historians and political biography of South African parliamentary politics, 1910-1990 - Mouton, F. A. (Faculty of Humanities, University of the Free State, 2011)
Biography strengthens the historian’s attempts to decipher the behaviour of individuals and also provides a historical window on a certain era, contributing to our knowledge and understanding of the past. Biographical studies of those who were involved in parliamentary politics between 1910 and 1990, the prime ministers, presidents, cabinet ministers, party leaders, humble backbenchers and unsuccessful parliamentary candidates can help to explain why the white minority, after decades of acquiescing the abuse of South Africa’s limited democratic tradition, decided to peacefully surrender its political power. And yet, despite the proven value of political biography in the United States and Britain, the library shelves of South African universities are bare of biographies on pre-1990 parliamentary politicians by professional historians. This article explains the reasons for this dearth of biographies, as well as the reasons why it is essential for professional historians to write them and concludes with a recommendation on how such biographies should be written.
Keywords: Biographical studies; Parliamentary politicians; Professional historians; Political biographies; South African history